2007
DOI: 10.1007/s11136-006-9164-2
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life, health status and clinical outcomes in Type 2 diabetes patients

Abstract: The fifth author's name was incorrectly coded for abstracting and indexing purposes in the original publication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
66
1
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(87 citation statements)
references
References 0 publications
19
66
1
1
Order By: Relevance
“…Two other studies reporting β coefficients derived from regression analyses did not find a significant association between depression and hospitalisation rates in patients with diabetes [25,37]. One study reported insufficient information to compute effect sizes [44]. Another study reported a decreased hospital admission rate directly following an emergency department visit [36].…”
Section: Direct Costsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two other studies reporting β coefficients derived from regression analyses did not find a significant association between depression and hospitalisation rates in patients with diabetes [25,37]. One study reported insufficient information to compute effect sizes [44]. Another study reported a decreased hospital admission rate directly following an emergency department visit [36].…”
Section: Direct Costsmentioning
confidence: 99%
“…In most cases, depression was studied (n=27) [4, 8, 9, 14-16, 18, 20, 21, 23, 25-31, 33, 34, 37, 39-42, 44-46], followed by mental disorders not further specified (n=5) [6,7,9,19,43], anxiety disorders (n=4) [9,14,18,36] and posttraumatic stress disorder (PTSD) (n=3) [14,18,45] (ESM Table 1 [15,31,39,44]. Healthcare costs were examined in various facets in the studies included.…”
Section: Characteristics Of Primary Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with T2DM are characterized by high adiposity and reduced fitness, which are also important predictors of Health-related Quality of Life (HRQoL) (2). Despite pharmacological strategies that can modulate many of the factors associated with the disease, T2DM-derived complications are common and have a significant impact in HRQoL, especially with respect to physical function (3) and depression (4).…”
Section: Introductionmentioning
confidence: 99%